Regional Collaboration on IT-Enabled Services : Smart Strategies for Jobs & Growth in South Asia - Ahmed, Sadiq; May, Ernesto; Bell, Simon C.; Haththotuwa, Manju (Colombo: World Bank, 2017)
The new millennium catalyzed a shift in the focus of South Asian economies to the service sector. The South Asian countries share many common characteristics - a young population, familiarity with the English language, and an emphasis on quantitative skills at the school level. This report on "Regional Collaboration on Information Technology (IT) Enabled Services-Smart Strategies for Jobs and Growth in South Asia" was initiated by the South Asia regional programs and South Asia poverty reduction, economic policy, finance and private sector development unit. It responds to a need expressed by our client countries for World Bank support to build their capability in the IT enabled services sector. The current study was commissioned with a view to facilitate their efforts through regional collaboration. This study suggests collaborative initiatives that could drive the growth of the industry through a two pronged approach: increase business through joint promotional activities, sub-contracting of work, building common standards and world class business practices; and develop supply side resources such as skills, support infrastructure and enabling policies. This study makes practical recommendations for collaborative growth between the countries in South Asia, who aspire to become the region of choice for global outsourcing.